Enhanced physicochemical properties of polydimethylsiloxane based microfluidic devices and thin films by incorporating synthetic micro-diamond. Issue 1 (December 2017) - Waheed, Sidra; Cabot, Joan; Macdonald, Niall; Kalsoom, Umme; Farajikhah, Syamak; Innis, Peter; Nesterenko, Pavel; Lewis, Trevor; Breadmore, Michael; Paull, Brett
Abstract Synthetic micro-diamond-polydimethylsiloxane (PDMS) composite microfluidic chips and thin films were produced using indirect 3D printing and spin coating fabrication techniques. Microfluidic chips containing up to 60 wt% micro-diamond were successfully cast and bonded. Physicochemical properties, including the dispersion pattern, hydrophobicity, chemical structure, elasticity and thermal characteristics of both chip and films were investigated. Scanning electron microscopy indicated that the micro-diamond particles were embedded and interconnected within the bulk material of the cast microfluidic chip, whereas in the case of thin films their increased presence at the polymer surface resulted in a reduced hydrophobicity of the composite. The elastic modulus increased from 1.28 for a PDMS control, to 4.42 MPa for the 60 wt% composite, along with a three-fold increase in thermal conductivity, from 0.15 to 0.45 W m−1 K−1 . Within the fluidic chips, micro-diamond incorporation enhanced heat dissipation by efficient transfer of heat from within the channels to the surrounding substrate. At a flow rate of 1000 μL/min, the gradient achieved for the 60 wt% composite chip equalled a 9.8 °C drop across a 3 cm long channel, more than twice that observed with the PDMS control chip.